Intraocular Lens dislocation mimicking an intraocular iris - Machado Soares, Ricardo (2022)
An 86-year-old woman with history of bilateral phacoemulsification (13 years prior), diabetic retinopathy sub- mitted to several treatments (pan-retinal photocoagulation, anti-VEGF intravitreal injections, and bilateral pars plana vitrectomy) and low visual acuity in the left eye (OS) due to retinal fibrosis, presented to the emergency ward with complaints of diminished visual acuity in her right eye (OD). On examination, her best-corrected visual acuity (BCVA) was hand motion in the OD and counting fingers in the OS. Fundoscopy of OD revealed a posteriorly dislocated three-piece intraocular lens (IOL) inside the capsular bag. During pars plana vitrectomy, the disposition of the IOL alongside the anterior capsule’s phimosis and Soemmering’s ring mimicked a light blue iris (Fig. 1). The IOL/capsular bag complex was removed and replaced with an aphakic iris-claw intraocular lens, improving her OD BCVA to 20/25. Lens epithelial cells are involved in the pathogenesis of anterior capsule fibrosis and posterior capsule opacification following cataract surgery.1 In 1928, Soemmering first described a ring of cortical fibers between the posterior capsule and the borders of the anterior capsule remnant, hence the name Soemmering’s ring.2,3 This finding is explained by the active proliferation of equatorial epithelial cells leading to an accumulation of new lens fibers between the equator and the anterior capsule margin/IOL optic.1,4 In contrast, the anterior epithelial cells undergo fibrous metaplasia leading to fibrosis of the anterior capsule, which leads to capsule phimosis in cases of small capsulorhexis.1